SEKOLAH SEBAGAI SARANA SOSIALISASI DAN PERKEMBANGAN PESERTA DIDIK - R. Dinul Qoyyimah, R; Delisa, Delisa; Ubabuddin, Ubabuddin (ILJ: Islamic Learning Journal, 2024)
This article discusses the role of schools as important socialization agents in shaping the social, emotional and intellectual development of individuals. Schools serve as dynamic environments where students interact with peers, educators and society at large, contributing to the formation of their social identities and values. This research uses the literature method, with documentary data collection and analysis using content analysis. The results state that the socialization process at school is complex, encompassing formal and informal interactions that influence students' communication, cooperation and adaptability skills. In addition, schools play an important role in transmitting cultural norms, fostering a sense of civic responsibility, and preparing individuals for active participation in society. Understanding school as the primary site of socialization provides a deep understanding of its significance in shaping individuals who are balanced personalities and able to deal with the complexities of the social world.